1979
DOI: 10.3109/01050397909076296
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically Evoked Potential: Dependence Upon Age

Abstract: The slow components of the potentials evoked acoustically by pure tones (1 kHz, 0 to 90 dB HL) were compared between two groups of subjects. All subjects of one group were 22 years old; the members of the other group had an average age of 63 years. The P2-latencies of the older subjects were significantly shorter for 60, 75 and 90 dB HL than those of the younger group. This finding was interpreted as a sign of a decreased efferent inhibition of several nuclei of the auditory pathway in the older subjects. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Papancoulaou et al (1984), Tremblay et al (2004), and Goodin (1978) found amplitudes to decrease with increasing age while Pfefferbaum et al (1980) Kim et al (Kim et al 2012) and Polich (1997) found signficant increases or trends toward larger amplitudes with increasing age. Finally, Harris et al (2008) Laffont et al (1989) and Spink et al (1979) found no effects of age. Most studies of auditory senescence in general, and of N1-P2 in particular, are afflicted by small samples and inadequate control for hearing loss, which typically accompanies aging and can confound estimated aging effects on N1-P2.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Papancoulaou et al (1984), Tremblay et al (2004), and Goodin (1978) found amplitudes to decrease with increasing age while Pfefferbaum et al (1980) Kim et al (Kim et al 2012) and Polich (1997) found signficant increases or trends toward larger amplitudes with increasing age. Finally, Harris et al (2008) Laffont et al (1989) and Spink et al (1979) found no effects of age. Most studies of auditory senescence in general, and of N1-P2 in particular, are afflicted by small samples and inadequate control for hearing loss, which typically accompanies aging and can confound estimated aging effects on N1-P2.…”
Section: Introductionmentioning
confidence: 87%
“…Most found that N1 and/or P2 latencies increased with increasing age (Papancoulaou et al 1984; Vanhanen et al 1996; Tremblay et al 2004; Harris et al 2007; Harris et al 2008; Lijffijt et al 2009; Kim et al 2012) though some did not (Spink et al 1979; Laffont et al 1989). N1 and/or P2 amplitude changes with age were perhaps even more variable.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Spink et al [18] studied acoustically evoked potentials and found that the slow components of auditory evoked potentials in the elderly were shorter than those of a younger group. They inter preted their findings as a sign of a decreased efferent inhi bition of several nuclei of the auditory pathway in the old er subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Goodin et al, (1978) reported a similar finding in a comparable subject population and experimental situation. Spink et al, (1979) examined the effects of different stimulus intensities on a small sample of elderly (mean age 63) and young (mean age 22) adults. Only subjects with hearing loss less than 10 dB at 1000 Hz were included, and stimuli were presented at intensities relative to SL.…”
Section: Age Effects On Sensory Epsmentioning
confidence: 99%